Contemporary video-based methods in cardiovascular surgical education - Balazs C. Lengyel, MD; Austin R. Shelton, MBE; Stuart J. Corr, BEng, MEng, MA, PhD; Alan B. Lumsden, MD, ChB, FACS, RVT, FRCS (JVS-Vascular Insights)
Over the past two decades, the digital revolution has transformed medical care and education. The digitization of video, imaging, and patient care lends itself to being integrated into surgical education easily. Video hosting sites such as YouTube permit the democratization of educational products, such that anyone in the world with Internet connectivity can have access to high-quality education, provided it is made available freely. This shift was further accelerated by the COVID-19 pandemic, which forced educators to adopt new multimedia technologies. However, this ease of access comes with a secondary set of issues, namely, ensuring quality and accuracy. Establishing a brand that is synonymous with educational quality has been a focus for DeBakey Cardiovascular Education. Although the scope of vascular surgery has and continues to explode, it reveals opportunities and challenges: opportunities to expand vascular care offerings and challenges in maintaining access to unbiased educational resources and supporting the performance of declining but vitally important open procedures, such as aneurysm repair. Multimodality educational modules can help to provide uniformity in evidence-based care delivery and support, while reducing geographical and financial disparities. Video-based educational methods, like videotaped procedures, propagate universal access to all kinds of techniques and therapeutic approaches. However, this educational approach includes not only traditional review of procedural videos and cases, but also new teaching methods like remote support through audiovisual communication and evolving technologies like immersive virtual reality simulations. These tools cater to a generation of new students consisting of digital natives, for whom digital platforms are second nature. Videos also serve as a source of data, enabling detailed, objective evaluation and feedback. With the integration of state-of-the-art artificial intelligence technologies, the potential applications of video-based methods seem to be limitless. This article explores contemporary video-based educational methods and their applications with a focus on cardiovascular surgical education.